Space-time distribution of temperature inversions in the Arctic atmospheric boundary layer - A. P. Nagurny
An increase in the amplitude and frequency of temperature inversions in the boundary layer (1.5 km above the Earth's surface) in the Arctic was detected using aerological data from the Russian ice stations during the interval 1954–1987.